UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MELALUI VARIASI PEMBELAJARAN - Jamaiah, Jamaiah; Triansyah, Andika; Puspa, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is the understanding of basic passing under the material can not dikuasi well is to know the improvement of passing learning outcomes under melalaui direct learning model assisted media on the fourth grade students of Elementary School 3 Gandis Hilir. In accordance with research objectives, then this research using the type of research "classroom action research" (research follow class). the subjects used in this study are grade IV SDN 3 Gandis Hilir as many as 26 students. Application of the passing down learning method through the model It is evident that there is an increase in the lower passing learning outcomes which is quite good, that is on the pre-implementation of the average value of 57.8 with the percentage of mastery of 17%. While the cycle I nilia averaged 72.08 with a complete percentage of 42.1%. then the average value of II is with the percentage of completeness of 92.1%.Â Keywords: Passing Down, Direct Learning Model Assisted Media